PENGARUH STABILITAS KADAR TRIGLISERIDA PADA SERUM SEGERA DIPERIKSA DAN DITUNDA 7 HARI PADA SUHU 2-8â—¦C: effect of triglyceride levels in serum which were immediately examined and delayed for 7 days at temperature of 2-8oC - Asrori Asrori; Iis Afriayani94 (Klinikal Sains : Jurnal Analis Kesehatan, 2023)
Examination of triglyceride levels using serum specimens is recommended to be examined immediately, but the examination can be delayed due to factors such as power outages and equipment damage. Deferred serum should be stored in a proper manner. Storage of specimens is one of the pre-analytic stages with a large risk of error. Research Objectives: knowing effect of triglyceride levels in serum which were immediately examined and delayed for 7 days at temperature of 2-8oC. Research method: This research is experimental design with pre-test and post-test design. The research population, namely students of level 1 and 2 of the Department of Medical Laboratory Technology, Poltekkes Kemenkes Palembang, amounted to 221 people. The sampling technique used random sampling. Triglyceride levels were checked using the Biosystem-350 tool. Data analysis using Wilcoxon test. Results: the average serum triglyceride level immediately checked was 73.43mg/dl, the average serum triglyceride level was delayed 7 days at temperature of 2-8oC was 72.63mg/dl. The results of the Wilcoxon test data analysis obtained a Pvalue =0.493. Conclusion: There is no difference in the average results of the examination of triglyceride levels in serum which are immediately examined and delayed for 7 days at temperature of 2-8oC